The Frontiers of Serrated Polyps. (January 2022) - Bell, Phoenix D.; Anderson, Joseph C.; Srivastava, Amitabh
Abstract : The serrated pathway of carcinogenesis has been the subject of intense investigation over the past 2 decades, but many gaps in our understanding still need to be resolved. Serrated polyp precursors include hyperplastic polyps, sessile serrated polyps, and traditional serrated adenomas. These are considered discrete entities, but there is emerging molecular data to suggest that they may be more closely related to each other than currently believed. The recent US Multi-Society Task Force surveillance guidelines for patients with serrated polyps are admittedly based on low quality evidence. In this brief review, we discuss the limitations in endoscopic detection and pathologic interpretation of serrated polyps and the implications of these diagnostic difficulties on risk prediction and postpolypectomy surveillance recommendations.